Development and evaluation of an autonomous camera control algorithm on the da Vinci Surgical System. Issue 2 (27th December 2019) - Eslamian, Shahab; Reisner, Luke A.; Pandya, Abhilash K.
Abstract: Background: Manual control of the camera arm in telerobotic surgical systems requires the surgeon to repeatedly interrupt the flow of the surgery. During surgery, there are instances when one or even both tools can drift out of the field of view. These issues may lead to increased workload and potential errors. Methods: We performed a 20‐participant subject study (including four surgeons) to compare different methods of camera control on a customized da Vinci Surgical System. We tested (a) an autonomous camera algorithm, (b) standard clutched control, and (c) an experienced camera operator using a joystick. Results: The automated algorithm surpassed the traditional method of clutched camera control in measures of userperceived workload, efficiency, and progress. Additionally, it was consistently able to generate more centered and appropriately zoomed viewpoints than the other methods while keeping both tools safely inside the camera's field of view. Conclusions: Clinical systems of the future should consider automating the camera control aspects of robotic surgery.